(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we look at the stochastic coupled Schrödinger-KdV equations with conformable derivative operator (SCS-KdVEs-CDO). By using the Sardar subequation method (SS-method), we can obtain results such as periodic soliton, bright soliton, dark-bright soliton and singular soliton. Some previous solutions of coupled Schrödinger-KdV equations are obtained when the order of derivatives is integer and noise is ignored. Due to the important applications of the coupled Schrödinger-KdV equations in dusty plasma, such as dust-acoustic waves, electromagnetic waves, and Langmuir waves, these obtained solutions might be utilized to the analysis of many fundamental physical phenomena. Furthermore, the effects of the conformable derivative operator and the noise term on the analytical solution of the SCS-KdVEs-CDO were illustrated by simulating some solutions via the MATLAB program.